2015
DOI: 10.1111/adj.12241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel bioactive glass-ceramic on dentinal tubule occlusion: anin vitrostudy

Abstract: Background: This in vitro study aimed to assess the ability and efficacy of HX-BGC, a novel bioactive glass-ceramic (SiO 2 -P 2 O 5 -CaO-Na 2 O-SrO), to reduce dentine tubule permeability. Methods: Dentine discs from human third molars were etched and randomly allocated into five groups: Group 1 -distilled water; Group 2 -Sensodyne Repair toothpaste (containing NovaMin®); Group 3 -HX-BGC toothpaste (containing 7.5% HX-BGC); Group 4 -control toothpaste (without HX-BGC); and Group 5 -HX-BGC powder. Specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 40 publications
2
43
0
7
Order By: Relevance
“…When BG has been added to other carriers, such as toothpastes, it has been demonstrated that the dentin tubule occlusion layer formed is resistant to acid challenge 5 , and reduces significantly dentine permeability under simulated oral environment 30 . In addition, it has been suggested that the apatite rods formed into dentine tubules after brushing with nBGs slurries would have excellent retention 4 .…”
Section: Discussionmentioning
confidence: 99%
“…When BG has been added to other carriers, such as toothpastes, it has been demonstrated that the dentin tubule occlusion layer formed is resistant to acid challenge 5 , and reduces significantly dentine permeability under simulated oral environment 30 . In addition, it has been suggested that the apatite rods formed into dentine tubules after brushing with nBGs slurries would have excellent retention 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The highest reduction in dentine permeability was observed after 7 days of treatment . Figure shows the formation of apatite‐like crystals inside dentine tubules and on its surface after brushing of the dentine with toothpaste containing bioactive glass‐ceramic . One interesting advantage presented by glass‐ceramics in this application is that because these materials are fully crystalline, they do not present sharp cutting surfaces.…”
Section: Bioactive Dental Glass‐ceramics (Bdgcs)mentioning
confidence: 96%
“…Bioactive glass‐ceramic toothpaste significantly and immediately lowered dentine permeability. The highest reduction in dentine permeability was observed after 7 days of treatment . Figure shows the formation of apatite‐like crystals inside dentine tubules and on its surface after brushing of the dentine with toothpaste containing bioactive glass‐ceramic .…”
Section: Bioactive Dental Glass‐ceramics (Bdgcs)mentioning
confidence: 98%
See 2 more Smart Citations